2014
DOI: 10.1371/journal.pone.0105712
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Delivery Method on Neuroprotection by Bone Marrow Mononuclear Cell Therapy following Ventral Root Reimplantation with Fibrin Sealant

Abstract: The present work compared the local injection of mononuclear cells to the spinal cord lateral funiculus with the alternative approach of local delivery with fibrin sealant after ventral root avulsion (VRA) and reimplantation. For that, female adult Lewis rats were divided into the following groups: avulsion only, reimplantation with fibrin sealant; root repair with fibrin sealant associated with mononuclear cells; and repair with fibrin sealant and injected mononuclear cells. Cell therapy resulted in greater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
24
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
9
24
1
2
Order By: Relevance
“…This indicates that the fibrin sealant implant provided conditions for regeneration of nerve fibers, resulting in a close to normal “g” ratio distribution. These results are in accordance with already published data by our group, where improvement in motor function was observed at 12 weeks after reimplantation of avulsioned roots [ 18 , 27 ]. MC treatment, however, resulted in decreased RZG, which will be addressed in future short-term analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the fibrin sealant implant provided conditions for regeneration of nerve fibers, resulting in a close to normal “g” ratio distribution. These results are in accordance with already published data by our group, where improvement in motor function was observed at 12 weeks after reimplantation of avulsioned roots [ 18 , 27 ]. MC treatment, however, resulted in decreased RZG, which will be addressed in future short-term analysis.…”
Section: Discussionsupporting
confidence: 93%
“…The results were observed by immunohistochemistry, in a semiquantitative fashion, indicating a significant enhancement of root axonal regrowth, two weeks after surgery. Such results are in line with a recent work from our lab, using mononuclear cells from the bone marrow [ 18 ]. Nevertheless, we have shown that the acute positive results of cell therapy do not last for more than four weeks, indicating that additional cell administration may be necessary to sustain the protective results.…”
Section: Discussionsupporting
confidence: 92%
“…This may be achieved by stem cell therapy that has shown particularly important positive effects following nervous system injury [ 28 37 ]. In this regard, we have already shown evidence that mononuclear cell therapy produced neuroprotection, preservation of synapses in the spinal cord, and reduction of glial reaction following dorsal and ventral horn adult lesion [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, translational research generates an increase in the capacity for health research with an interdisciplinary and multidisciplinary approach, forming, training and integrating a new generation of researchers [4]. This new biopharmaceutical has enormous potential application in Medicine and Dentistry [10], which presents greater purity, lesser toxicity and greater adhesiveness [11][12][13][14][15].…”
Section: Short Communicationmentioning
confidence: 99%